Government support and firm innovation performance: Empirical analysis of 343 innovative enterprises in China. Issue 1 (7th April 2015) - Wei, Jiuchang; Liu, Yang
Abstract : Purpose: – This paper aims to examine the effect of government support on the innovation performance of firms in the Chinese context. Design/methodology/approach: – We divided government support into vertical support and horizontal support, and adopted an empirical research approach in this study. We collected the data of 343 enterprises in China that had been identified as innovative enterprises, including their characteristic data, government support data and patent data. Negative binomial regression was used to quantitatively examine the relationship between government support and the innovation performance of firms. Findings: – Both vertical support in the form of direct research and development (R&D) subsidies and horizontal support in the form of regional innovation policy positively influence the innovation performance of firms. In addition, direct R&D subsidies are more likely to experience the enhanced benefits of carrying out tax credit policy on the innovation performance of firms. Originality/value: – This study contributed to the innovation literature by distinguishing two types of government support, namely, vertical support and horizontal support, and assessing the effects of government support on firm innovation in the Chinese context.